Feedback to Prepare EMS Teams to Manage Infected Patients with COVID-19: A Case Series. Issue 4 (8th August 2020) - Ghazali, Daniel Aiham; Ouersighni, Amina; Gay, Matthieu; Audebault, Virginie; Pavlovsky, Thomas; Casalino, Enrique
Abstract: Coronavirus Disease 2019 (COVID-19), a new respiratory disease, is spreading globally. In France, Emergency Medical Service (EMS) teams are mobile medicalized resuscitation teams composed of emergency physician, nurse or anesthesiologist nurse, ambulance driver, and resident. Four types of clinical cases are presented here because they have led these EMS teams to change practices in their management of patients suspected of COVID-19 infection: cardiac arrest, hypoxia on an acute pneumonia, acute chronic obstructive pulmonary disease (COPD) exacerbation with respiratory and hemodynamic disorders, and upper function disorders in a patient in a long-term care facility. The last case raised the question of COVID-19 cases with atypical forms in elderly subjects. Providers were contaminated during the management of these patients. These cases highlighted the need to review the way these EMS teams are responding to the COVID-19 pandemic, in view of heightening potential for early identification of suspicious cases, and of reinforcing the application of staff protection equipment to limit risk of contamination.